The Professional as the Executive's Ethical Aide-de-Camp - Joseph A. Raelin (Academy of Management Perspectives, 1987)
In light of recent managerial oversights such as those connected with the Challenger space shuttle disaster, having executives rely more on their professionals might serve to improve their organization's ethical consciousness. Although the professional record on corporate ethical behavior is by no means exemplary, the functional basis of the professions, especially the support rendered members through their professional associations and codes, is sufficient to make them potential watchdogs of corporate misconduct. The IEEE, for example, has taken steps to defend engineers who, in acting professionally to defend the public interest, are subject to arbitrary reprisals from employers. Executives, however, need to lead in encouraging professionals to follow their best instincts in supporting an ethical position within the enterprise. According to Raelin, three steps executives can take in this regard are (1) raising an ethical consciousness, (2) setting up an ethical process and structure, and (3) institutionalizing the structure. The first step involves a pronouncement from the CEO that the company is forever committed to a free and open exchange of ideas, including discretionary opinions from the professional staff. It also consists of an articulation of social and ethical goals that share the corporate agenda with economic goals. The next steps dictate how the organization goes about meeting those goals and what decision-making procedures and structures are to be adopted in carrying out such a social policy. By institutionalization, professionals and operating managers have incorporated ethical objectives into their day-to-day practice.
Keywords: L84; J44; J24; D63; O15; M12; M14; 330; Professional ethics; Professional associations; Managing professionals; Professional autonomy